2019
DOI: 10.1016/j.sjbs.2019.06.017
|View full text |Cite
|
Sign up to set email alerts
|

The mechanism of lipopolysaccharide administration-induced cognitive function impairment caused by glucose metabolism disorder in adult rats

Abstract: ObjectiveThis essay aims to make investigation on the mechanism of glucose metabolism disorder and Lipopolysaccharide administration-induced cognitive function impairment in adult rats with surgery. Methods: Divide the objects, 40 male Sprague-Dawley rats at the age of 9 months, into 4 groups. Provide unilateral nephrectomy surgery and/or lipopolysaccharide intraperitoneal injection. Postoperative cognitive function evaluation would be tested by the Morris water maze. Rats with Postoperative Cognitive Dysfunct… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(2 citation statements)
references
References 32 publications
1
1
0
Order By: Relevance
“…Furthermore, as a product of bacterial imbalance, LPS increased BBB permeability and induced the release of pro-inflammatory cytokines including TNF-α, which exacerbates the central inflammatory response. In this study, we observed that serum LPS and DAO levels were higher in the APP/AP1-C and WT-C groups than in groups that received EA intervention, indicating gut barrier impairment (Du et al, 2019). Interestingly, our study detected the preserved integrity of both the intestinal barrier and BBB in APP/PS1-E mice, which are consistent with the findings of Wang et al (2020) and Zhao et al (2022).…”
Section: Discussionsupporting
confidence: 88%
“…Furthermore, as a product of bacterial imbalance, LPS increased BBB permeability and induced the release of pro-inflammatory cytokines including TNF-α, which exacerbates the central inflammatory response. In this study, we observed that serum LPS and DAO levels were higher in the APP/AP1-C and WT-C groups than in groups that received EA intervention, indicating gut barrier impairment (Du et al, 2019). Interestingly, our study detected the preserved integrity of both the intestinal barrier and BBB in APP/PS1-E mice, which are consistent with the findings of Wang et al (2020) and Zhao et al (2022).…”
Section: Discussionsupporting
confidence: 88%
“…In the clinical setting, POCD is usually diagnosed based on the patient’s complaint and the change of neuropsychological scale score. 3 However, a traditional scale like a Mini-Mental State Examination is considered not sensitive enough to detect changes in cognition, compared with other imaging methods, like Fluoro-2-deoxy-D-glucose PET (18F-FDG) PET, 13 14 while the latter one is expensive and radioactive. Clinicians are expecting novel biomarkers, yet few studies could achieve long-term postoperative tracking and evaluation of patients, as well as observe the impact on cognition by perioperative biophilic VR intervention, we will apply the method of Montreal Cognitive Assessment (MoCA) test as recent study suggested that the 2 scores rule with MoCA had the best combination of sensitivity and specificity to diagnose delayed neurocognitive recovery.…”
Section: Introductionmentioning
confidence: 99%